Analisis Interjeksi Yang Digunakan Dalam Naskah Film “Turning Red” - Desi, Desi; Oktoma, Erwin; Solihat, Dadang (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the types and meanings of the interjections used in the movie script Turning Red. This study uses a qualitative descriptive research design because it investigates the interjection utterances used in the movie script Turning Red. In data analysis, the researcher found dialogue interjection in the movie script Turning Red. Then, the researcher identified the types and meanings of the interjection in each utterance based on the theory. After that, the researcher classifies the types and meanings of the dominant interjection in the movie script Turning Red and the researcher also calculates the data and makes conclusions based on the data analysis from the data analysis, the results showed that: there were 197 interjection words in the Turning Red movie script. The types of interjection that stands out in the Turning Red movie script is Primary Interjection while the most dominant meanings of interjection is dismay. Interjection, movie script, turning red